2020
DOI: 10.1128/mbio.03407-19
|View full text |Cite
|
Sign up to set email alerts
|

Using Colonization Assays and Comparative Genomics To Discover Symbiosis Behaviors and Factors in Vibrio fischeri

Abstract: The luminous marine Gram-negative bacterium Vibrio (Aliivibrio) fischeri is the natural light organ symbiont of several squid species, including the Hawaiian bobtail squid, Euprymna scolopes, and the Japanese bobtail squid, Euprymna morsei. Work with E. scolopes has shown how the bacteria establish their niche in the light organ of the newly hatched host. Two types of V. fischeri strains have been distinguished based upon their behavior in cocolonization competition assays in juvenile E. scolopes, i.e., (i) ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…A large predicted lipoprotein is coordinately expressed with T6SS proteins. V. fischeri use several competitive mechanisms to compete for limited space within the host during colonization [51][52][53], including a strain-specific T6SS located on a genomic island on chromosome II (T6SS2) (Fig 1b) [21]. T6SS2 prevents incompatible strains from coexisting within the same crypt space, thereby shaping the diversity and spatial structure of the microbial community within a natural host, and this T6SS-mediated competition can be visualized and quantified in culture and in the host [21].…”
Section: Resultsmentioning
confidence: 99%
“…A large predicted lipoprotein is coordinately expressed with T6SS proteins. V. fischeri use several competitive mechanisms to compete for limited space within the host during colonization [51][52][53], including a strain-specific T6SS located on a genomic island on chromosome II (T6SS2) (Fig 1b) [21]. T6SS2 prevents incompatible strains from coexisting within the same crypt space, thereby shaping the diversity and spatial structure of the microbial community within a natural host, and this T6SS-mediated competition can be visualized and quantified in culture and in the host [21].…”
Section: Resultsmentioning
confidence: 99%
“…A mutation shared among these resistant clones was a missense mutation encoding an E183V substitution in the glycosyltransferase gene VF_0175, which is part of the locus (VF_0157-80) responsible for production of exopolysaccharide (EPS) by strain ES114 (Bennett et al, 2020). Homologs of VF_0175 are predicted in many, but not all, V. fischeri genomes, suggesting that this gene may be under selection in different environmental contexts (Bongrand et al, 2020). Targeted deletion of VF_0175 or VF_0157-80, together with the provision of VF_0175 or VF_0175(E183V) in trans, confirmed that a functional copy of this gene in the context of a full-length EPS locus is necessary for ϕHNL01 infection ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…While we found that some membrane components are not required for ϕHNL01 predation ( e.g ., mutations in waaL and eptA , both of which are involved in lipooligosaccharide decoration, do not affect ES114 susceptibility to ϕHNL01; Table S1 ), we did identify other envelope-based infection resistance ( e.g ., mutations in the EPS gene cluster render ES114 resistant to ϕHNL01), suggesting some general shared aspects of phage infection between V. cholerae and V. fischeri . Because V. fischeri ES114 is the only ϕHNL01 host we identified, broader studies of V. fischeri phages around different areas of Hawaiʻi and other geographic regions where this species is endemic will reveal the ubiquity of related phages amongst different host populations, as well as the breadth of resistance mechanisms V. fischeri uses amongst its various symbiotic relationships (Bongrand et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that multiple strains can cocolonize the squid LO and that they do so at different rates ( 60 62 ). More recent studies have focused on deciphering the specific mechanisms that result in differing colonization behavior ( 63 , 64 ). The barcode-tagged mutagenesis method presented here can be applied to generate uniquely tagged WT or mutant strains of the various phylogenetically distinct V. fischeri strains and assayed in multiplexed format during squid colonization using BarSeq.…”
Section: Discussionmentioning
confidence: 99%